2018
DOI: 10.1111/chd.12731
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of perimembranous ventricular septal defects utilizing almost ideal Amplatzer Duct Occluder II: Why limitation in sizes?

Abstract: Aim:The purpose of this study is to describe the special aspects of perimembranous ventricular septal defects (pmVSD) closure by utilizing Amplatzer Duct Occluder II (ADO II) devices with a rational request for bigger ADO-II sizes, based on our experience in transcatheter device closure of pmVSD. Methods and Results: At our institution, placement of an ADO II device was used in 15 patients with pmVSD; the patients' age ranged between 6 months and 20 years.The indications for closure were CHF (n = 4), hemodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
0
17
0
3
Order By: Relevance
“…e most serious arrhythmia is complete atrioventricular block, with an incidence of 1% to 5% [19][20][21]. ose who cannot recover after treatment with methylprednisolone or temporary pacemaker need permanent pacemaker treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…e most serious arrhythmia is complete atrioventricular block, with an incidence of 1% to 5% [19][20][21]. ose who cannot recover after treatment with methylprednisolone or temporary pacemaker need permanent pacemaker treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Se opta por el cierre percutáneo al tener experiencia en el cierre de las comunicaciones interventriculares (CIV) perimembranosas con el oclusor ADO II y porque la técnica para cerrar los defectos de Gerbode es la misma que para el cierre de la CIV perimembranosa (5). Se elige este dispositivo porque tiene un bajo perfil, por lo que necesita una vaina más pequeña que otros dispositivos, lo que supone una gran ventaja cuando se trata de pacientes pediátricos.…”
Section: Discussionunclassified
“…• Casos clínicos RETIC. 2020 (Mar); 3 (1): 23-26 cierre de la CIV y con la bibliografía, se elige un tamaño de dispositivo entre 0-1 mm mayor que el diámetro del defecto (5) . La mayor serie publicada de cierre de defectos de Gerbode congénitos también utiliza esta regla a la hora de escoger el tamaño del dispositivo (6) .…”
Section: Discussionunclassified
“…Complete atrioventricular block Cardiac dysrhythmias were other common complications, and cAVB was the most important among them. Nonetheless, the rate of cAVB in the 13 studies Esmaeili 18 El-Sisi 17 Fixed Overall…”
Section: Complication Rates Residual Shuntsmentioning
confidence: 99%
“…16 STATA version 15.0 (StataCorp LLC, College Station, Texas, United States) was used for all statistical analyses. results study characteristics A total of 150 studies were identified, of which 13 (with data for 478 participants) were included in this analysis (FiGURe 1) 7,8,10,11,[17][18][19][20][21][22][23][24] : 4 prospective studies, 4 retrospective studies, and 5 studies of uncertain types. The year of publication ranged from 2012 to 2019.…”
mentioning
confidence: 99%